KUALITAS AIR SUMUR GALIAN PINGGIR SUNGAI DI KELURAHAN LIDAK KECAMATAN ATAMBUA SELATAN KABUPATEN BELU - Lusi, Retnasari; Hasan, Muhammad Husain; Manek, Agustinus Hale (Universitas Nusa Cendana, 2023)
This research aims to:1). To determine the water quality of dug wells on the banks of a river used for drinking water needs in the dry season in the Lidak village river Atambua District, Belu Regency. Types of Qualitative Research. Which research focus stems from an inductive mindset, which is based on participatory objective observation of a symptom (phenomena) social. qualitative data in the form of descriptive details. If viewed from problems with the quality of water from dug wells and the distance of wells far from residential areas, then the type of research that leads to the study of physical geography, Data collection (procedure research) 1. Sampling point 2. Collection 3. Documentation. Laboratory test results on the quality of dug well water through 2 samples of dug well water on physical parameters and The bacteriological parameters indicated that the water from the two dug wells, namely well 1 and well 2, passed through physical parameters met the requirements while the bacteriological parameters did not meet the requirements, it was seen The results table shows the bacteriological high in the dug well water sample 1 has a yield of 75 MPN/100 ml in the maximum prescribed concentration (50 MPN/10 ml) in the bacteriological parameter Total coliform while the E coli parameter is 11 MPN/100 m from the specified maximum level (0 MPN/100 m), then 2 dug well water samples indicates a higher bacteriological level where the results of the table show dug well water 2 in bacteriological parameters, the total coliform was 460 MPN/100 ml of the maximum concentration specified. whereas in the bacteriolytic parameters of E coli as much as 60 MPN/100 ml this result showing the number of harmful bacteria present in the dug well water, total bacterology coliform and E coli Total coliform is a group of bacteria used as an indicator presence of dirt pollution. The total coliform in food or drink shows the possibility of harmful enteropathogenic and/or toxigenic microbes for health